2019
DOI: 10.1021/acsenergylett.9b01630
|View full text |Cite
|
Sign up to set email alerts
|

13.9% Efficiency Ternary Nonfullerene Organic Solar Cells Featuring Low-Structural Order

Abstract: The insufficient phase separation between polymer donors and non-fullerene acceptors (NFAs) featuring with low-structural orders disrupts efficient charge transport and increases charge recombination, consequently limits the maximum achievable power conversion efficiency (PCE) of organic solar cells (OSCs). Herein, an NFA IT-M has been added as the third component into the PBDB-T:m-INPOIC OSCs, and is shown to effectively tune the phase separation between donor and acceptor molecules, although all components i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Various publications have suggested that by adding a small amount of either D or A to a binary BHJ, the third component gives rise to balanced transport and increased solar cell performance. [31][32][33][34] The addition of a small amount of a fullerene molecule in polymer/non-fullerene solar cells has also been widely adopted to increase device performance and stability. As a relevant example, adding the fullerene PCBM to the blend of PM6 with Y6 led to a substantial increase in both the hole and electron mobilities.…”
Section: Resultsmentioning
confidence: 99%
“…Various publications have suggested that by adding a small amount of either D or A to a binary BHJ, the third component gives rise to balanced transport and increased solar cell performance. [31][32][33][34] The addition of a small amount of a fullerene molecule in polymer/non-fullerene solar cells has also been widely adopted to increase device performance and stability. As a relevant example, adding the fullerene PCBM to the blend of PM6 with Y6 led to a substantial increase in both the hole and electron mobilities.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, pristine DR8 film displays a quite different molecular assembly feature, i.e.,a strong (100) signal at 0.328 Å −1 was observed in the IP direction while a lamellar signal at 0.341 Å −1 in the OOP direction, suggesting mixed face‐on and edge‐on orientations in the film. [ 41 ] The binary PM6:ITC6‐4Cl blend film displays a preferential face‐on orientation, with a (100) lamellar stacking diffraction peak located at q xy = 0.307 Å −1 in the IP direction and a (010) π–π stacking peak at q z = 1.71 Å −1 in the OOP direction (Table S5, Supporting Information). Thus, the interlamellar spacing and π–π stacking distances are calculated to be 20.46 and 3.67 Å, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…[ 19 ] In detail, all blend exhibit a (100) lamellar packing diffraction peak at q xy = 0.28 Å −1 in IP directions with a lamellar distance of 22.44 Å, which is the characteristic of PBDB‐T. [ 52 ] Correspondingly, the crystal coherence length (CCL) of PBDB‐T:IPT2F‐TT blend is calculated to be 11.78 nm in IP direction, longer than IPT2F‐Ph‐ (11.31 nm) and IPT2F‐Th‐ (11.31 nm) based counterparts. Moreover, PBDB‐T:IPT2F‐TT blends exhibit the (010) ππ stacking diffraction peak in OOP direction at q z = 1.72 Å −1 , smaller than q z (1.75 Å) for PBDB‐T blends with IPT2F‐Ph, IPT2F‐Th, and IPT‐2F blends.…”
Section: Resultsmentioning
confidence: 99%